Simulation can replace part of speech-language pathology placement time: A randomised controlled trial. (2nd January 2021) - Hill, Anne E.; Ward, Elizabeth; Heard, Robert; McAllister, Sue; McCabe, Patricia; Penman, Adriana; Caird, Emma; Aldridge, Danielle; Baldac, Stacey; Cardell, Elizabeth; Davenport, Rachel; Davidson, Bronwyn; et al.
Abstract: Purpose: Simulation is increasingly used within speech-language pathology education. Research has primarily explored students' perceptions of learning in simulation. The aim of this study was to determine if speech-language pathology students achieved a statistically-equivalent level of competency when a mean of 20% of placement time was replaced with simulation compared to placements without a simulation component. Method: This non-inferiority randomised controlled trial involved students from six Australian universities. Students were randomised to either a simulation + traditional placement group attending 5 days of simulation prior to their traditional placement, or a traditional only placement group. Their end-placement clinical competency was assessed using Competency Assessment in Speech Pathology (COMPASS ® ). Result: Final data were available for 325 students: 150 students in traditional placements, 138 students in protocol-compliant simulation + traditional placements, and 37 students in non-protocol simulation + traditional placements. There were no statistically significant differences between groups (traditional vs protocol-compliant simulation + traditional Mann–Whitney–Wilcoxon z  = 1.23, df  = 286, p  = 0.22; traditional vs intention-to-treat simulation + traditional Mann–Whitney–Wilcoxon z  = 0.23, df  = 323, p  = 0.81). Conclusion: This research contributes to the evidence base which suggests that simulation can partially replace traditional placement time for speech-language pathology students without loss of competency, substantiating its value as an alternative placement model in speech-language pathology programmes.